KINERJA BALAI PENGEMBANGAN SDM dan PRODUK INDUSTRI KECIL MENENGAH (IKM) DINAS PERINDUSTRIAN dan PERDAGANGAN PROVINSI JAWA TENGAH - Harianja, Veronica Quillitta; Widowati, Nina (Journal of Public Policy and Management Review, 2015)
This research aims to analyze the performance of Human Resources Development and Small and Medium Product Office of Departments of Industry and Commerce of Central Java Province. This study used qualitative research methods. The informan of this research technique was used snowball. Performance of Human Resources Development and Small and Medium Product Office of Departments of Industry and Commerce of Central Java Province not shown optimal results. It can be seen from the mission has not accomplished, including about inaccuracy of the purpose of training with training materials that are not appropriate, as well as a lack of understanding of the wishes of the people, so it needs to be revisited workload of each employee so that vision and mission can be implemented optimally.